A "fivefold bottom line" approach of implementing and reporting corporate efforts in sustainable business practices. Issue 4 (3rd June 2014) - A.O. Dos Santos, Maria; Svensson, Göran; Padin, Carmen
Abstract : Purpose: – The purpose of this paper is to describe a "fivefold bottom line" approach in implementing and reporting corporate efforts of sustainable business practices. Design/methodology/approach: – This viewpoint from industry is based on the content analysis of the South African retail chain Woolworths. The data are gathered and derived from the company's comprehensive annual and sustainability reports from 2008 to 2011 and the company's press releases for this period focusing on their efforts of implementing and reporting sustainable business practices. Findings: – A lesson learned from the presented "fivefold bottom line" approach to implement and report their corporate efforts of sustainable business practices is that it is adapted to fit and make sense in a specific market and society. The triple bottom line approach is usually derived from, or commonly based upon, a western perspective on the market and society in literature. Research limitations/implications: – The authors argues that insights from industry of implementing and reporting sustainable business practices based upon different corporate "bottom line" approaches are required in literature. Practical implications: – The authors propose that the "triple bottom line" approach may need to be commonly adapted to the country and cultural context in focus, which is not normally done, but templates are used. Originality/value: – Triple bottom line reporting tends to follow common approaches how it is done. There is rarely seen adapted or modified "bottom line" approaches to specific market and societal characteristics in literature.